Endohepatology in the Management of Liver Diseases - Wang, Thomas J.; Singh, Ajaypal (Seminars in Liver Disease, 2025)
Endohepatology is an emerging field that encompasses various diagnostic and therapeutic endoscopic ultrasound (EUS) techniques for the management of liver disease. It encompasses diagnostic techniques for fibrosis staging and portal hypertension evaluation, as well as therapeutic interventions for conditions like variceal bleeding. Given the medical complexity and fragility that are often encountered in patients with liver disease, careful attention is of paramount importance to minimize risk and invasiveness when possible while extracting maximal value with a therapeutic intent. EUS-guided access to liver, bile ducts, and the hepatic vasculature provides the ability for diagnostic evaluation and interventions, which are not limited by body habitus and the need for central vascular access. Established EUS-guided techniques include liver biopsy, direct portal pressure gradient measurements, and gastric variceal coiling and injection therapies. More emerging techniques, including liver palpation, shear wave elastography, portal venous sampling, rectal variceal coiling, and partial splenic artery embolization, have also been described in the literature. This review details the rationale and evidence behind both established and emerging EUS-guided techniques, highlighting their current and potential future impact on endohepatology.
Keywords: diagnostic and therapeutic EUS; EUS-based techniques; portal hypertension; variceal bleeding; liver fibrosis evaluation